Analisis Representasi Konflik Keluarga dalam Film Perayaan Mati Rasa (2025) - Averil Sasha Audrey; Dian Hutami Rahmawati (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2026)
This study aims to analyze the representation of family conflict in the film Perayaan Mati Rasa using John Fiske's semiotic analysis through the levels of reality, representation, and ideology. This research employed a qualitative descriptive approach with a postpositivist paradigm. Data were collected through observations of scenes, dialogues, expressions, and visual elements related to family conflict. The results show that family conflict is represented through sibling rivalry, emotional neglect, silent treatment, authoritarian parenting, generational gaps, economic pressure, and differences in expectations between parents and children. At the reality level, conflict is shown through disappointed expressions, avoidant gestures, and silence. At the representation level, the film constructs conflict through closed communication and unequal power relations within the family. Meanwhile, at the ideological level, the film criticizes patriarchal culture, the expectation that the eldest child must always be strong, and the assumption that family is always a safe space for its members. This study concludes that family conflict in the film arises from failures in emotional communication, lack of empathy, and unequal family relationships.